Answer:
76.
Explanation:
Simplifying
-4(x + -26) = -200
Reorder the terms:
-4(-26 + x) = -200
(-26 * -4 + x * -4) = -200
(104 + -4x) = -200
Solving
104 + -4x = -200
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-104' to each side of the equation.
104 + -104 + -4x = -200 + -104
Combine like terms: 104 + -104 = 0
0 + -4x = -200 + -104
-4x = -200 + -104
Combine like terms: -200 + -104 = -304
-4x = -304
Divide each side by '-4'.
x = 76
Simplifying
x = 76